Hypotrophy of puppies against the background of developmental defects - Dmytrenko, N.; Kanivets, N.; Kravchenko, S.; Karysheva, L.; Perviy, A. (Scientific Progress & Innovations, 2024)
The concept of hypotrophy describes a disorder of development and growth of newborn animals and can be caused by improper conditions of the future breed during its life and during pregnancy, improper breeding work, the influence of teratogenic factors, and among domestic dogs, most often due to nutritional disorders of fetuses in the antenatal and puppies in the postnatal periods. This pathology is characterised by morphological and functional immaturity of the organs and systems of the newborn animal and is clinically manifested by its low resistance to exogenous factors: colostrum load, environmental conditions, opportunistic and pathogenic microflora. It was noted that the development of postnatal hypotrophy is facilitated by congenital malformations of puppies. In dogs of brachycephalic breeds, the most common intrauterine developmental defects include cleft palate and hydrocephalus (90 % and 40% of fatalities among newborn puppies, respectively). The specialised literature contains general information on the correlation of hypotrophic processes in puppies with developmental defects, but there are few publications on breed specifics. The aim of the study was to describe some anatomical and physiological parameters of pug and French bulldog puppies with hypotrophy against the background of hydrocephalus and cleft palate. It has been established that in the Lakomy Kusochek and Luizental dog kennels in 2016–2024, the mortality rate of newborn pug puppies was 10 %, of French bulldog puppies – 14 %, and cleft palate was observed in 22 % of the dead puppies. Clinically, hypotrophy in newborn puppies is manifested by low mobility and low growth rate. It was determined that the Apgar score in pug puppies among hypotrophic puppies was 1.5 times lower on average (p˂0.001) and 1.3 times lower in French bulldog puppies (p˂0.001). The growth coefficient was three times lower among pugs (p˂0.01) and 2.9 times lower among French bulldogs (p˂0.001). Body weight at birth among hypotrophics of both breeds was lower by 17.8 and 19.8 %, respectively (p˂0.001), and later the ratio of body weight of normal puppies to hypotrophic puppies also significantly decreased: on the first day - by 34.9 and 24.8 % (p˂0.001), on the second - by 40 and 34.3 % (p˂0.001), on the third – by 45.5 and 43.6 % (p˂0.001), on the fourth – by 48 and 51.2 % (p˂0.001), for the fifth – by 50.9 and 58.3 % (p˂0.001), for the seventh – by 56.6 and 68.4 % (p˂0.001), for the ninth – by 63.4 and 74.7 % (p˂0.001), for the 12th – for pug puppies by 71.1 (p˂0.001). The data obtained prove that congenital malformations (cleft palate and hydrocephalus) significantly contribute to the development of postnatal hypotrophy in pug and French bulldog puppies.